Ultra Sonographic Profile of Nephroblastoma at the University Clinics of Kinshasa (Global Journal of Medical Research, 2023)
Objective To describe the ultrasonographic profile of nephroblastoma diagnosed at the university clinics of Kinshasa Materials and methods This is a descriptive study it concerns 45 patients with Wilms tumor diagnosed by ultrasonography at the university clinics of Kinshasa from 2016 to 2021 i e an overall period of six years Two ultrasound scanners branded Phillips u-22 and Mindray DC-30 were used
Keywords: nephroblastoma; ultrasonography; pediatrics and histopathology